Optimizing suction blister epidermal graft technique in the surgical treatment of vitiligo - Gerson Dellatorre; Wagner Bertolini; Caio Cesar Silva de Castro (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Surgical management of vitiligo is considered an excellent terapeutic option for recalcitrant cases, provided the disease is stable and there is absence of Koebner phenomenom. Among surgical modalities, Suction Blister Epidermal Graft is a low cost and effective option (65 to 100% repigmentation can be achieved in up to 80% of patients). We describe how it can be optimized by using an alternative suction equipment, by customization of graft format and by application of an anesthetic technique that substantially reduces procedure time.